THE EFFECT OF CAPITAL EXPENDITURE, ENVIRONMENTAL PERFOMANCE, ENVIRONMENTAL MANAGEMENT SYSTEM, INSTITUTIONAL OWNERSHIP AND INDEPENDENT BOARD OF COMMISSIONERS ON CARBON EMISSION DISCLOSURE - Desvita, Lilla; Rahma, Yusro (Jurnal Akuntansi Bisnis, 2025)
Background: Climate change is a serious global threat. Indonesia has an important role in mitigation efforts. To address this issue, a joint effort is needed from the government, companies, and communities to reduce greenhouse gas emissions, encourage sustainable business practices, and raise awareness of the importance of protecting the environment.Objective: This study aims to test the influence of capital expenditure, environmental performance, environmental management system, institutional ownership, and independent board of commissioners on carbon emission disclosure.Research Methods: This study uses secondary data from annual reports and sustainability reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023 with a total of 105 data selected through a purposive sampling method. The analysis method used to test the hypothesis is multiple linear regression analysis using SPSS version 29.Research Result: The results of this study indicate that environmental performance and environmental management system have a significant positive effect on carbon emission disclosure. While capital expenditure, institutional ownership, and independent board of commissioners do not affect carbon emission disclosure.Authenticity/Novelty of Research: This study can contribute to additional literature related to research on carbon emission disclosure in non-financial companies in Indonesia which is still rarely studied. This study also re-evaluates the capital expenditure variable which still has different findings in previous studies and is considered relevant to the company's real actions in reducing environmental impacts and increasing carbon emission transparency.